The effect of television advertising speech on consumer behavior of Algerian women - KHALFALLAOUI, CHEMSEDIN (Journal of Social Sciences and Humanities, 2021)
Advertising has become a source of funding for many communication means, including television, which is considered the most influential media outlet on the audience of spectators because it contains sound, image, idea and text, which makes the television advertising message occupy the top in its impact on the psyche of consumers. Therefore, this field study aims to address a topic related to the influence of the television advertising discourse on the consumer behavior of Algerian women. The questionnaire was used as a tool to extract information from the study sample consisting of 60 individuals randomly selected from the original community. We concluded that the television advertising speech has a great role in influencing the consumer behavior of the study sample by attracting their attention, arousing their interest and creating their desires to buy the product, but this effect diminishes upon the purchase process.